GAMBARAN KEJADIAN POST DURAL PUNCTURE HEADACHE (PDPH) PADA PASIEN SECTIO CAESAREA DENGAN ANESTESI SPINAL DI RSU HAJI MEDAN: DESCRIPTION OF INCIDENT OF POST DURAL PUNCTURE HEADACHE (PDPH) IN CAESAREA SECTIO PATIENTS WITH SPINAL ANASTHESIA AT HAJI HOSPITAL MEDAN - Abdi, Nisrina Nabilah; Firmanda, Dody; Pane, Abdul Harris; Novasyra, Aulia (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2025)
Background: Post-Dural Puncture Headache (PDPH) is a complication that can occur after spinal anesthesia, typically characterized by a headache in the frontal or occipital regions, which is position-dependent, worsening when the patient stands and improving when the patient lies down. Objective: To determine the frequency distribution of post-dural puncture headache (PDPH) cases in patients undergoing cesarean section with spinal anesthesia at Haji General Hospital Medan. Methods : This study used a descriptive observational design with purposive sampling technique. A total of 36 samples were obtained from primary data through brief interviews and secondary data from medical records, specifically the patient's anesthesia status notes. The data were analyzed using univariate analysis. Results : Among the 3 samples that experienced post-dural puncture headache, 2 patients (66.7%) had a history of PDPH, and all three patients were in the age group of 19–40 years (100.0%). The majority of cases were found in the obesity I category (66.7%), with 1 case (33.3%) in the normal BMI category. Conclusion : From 36 samples of cesarean section patients with spinal anesthesia, 3 patients (8.3%) experienced post-dural puncture headache. AbstrakLatar belakang: Post-Dural Puncture Headache (PDPH) atau sakit kepala setelah anestesi spinal merupakan salah satu komplikasi yang dapat terjadi setelah anestesi spinal, biasanya ditandai dengan keluhan nyeri kepala di daerah frontal atau oksipital yang berhubungan dengan posisi, memberat saat pasien berdiri dan membaik saat pasien berbaring. Tujuan: Untuk mengetahui gambaran distribusi frekuensi kasus post dural puncture headache (PDPH) pada pasien sectio caesarea dengan anestesi spinal di RSU Haji Medan. Metode: Deskriptif observasional dengan teknik pengambilan sampel purposive sampling. Terdapat 36 sampel yang diperoleh dari data primer berupa wawancara singkat dan data sekunder yaitu rekam medis yang berupa catatan status anestesi pasien. Hasil data penelitian dianalisis menggunakan analisis univariat. Hasil: Dari 3 sampel yang menglami post dural puncture headache, ditemukan pasien yang memiliki riwayat PDPH sebanyak 2 orang (66.7%), ketiganya berada di kelompok usia 19 – 40 tahun (100.0%). Terjadi pada kategori BMI obesitas I sebanyak 2 orang (66,7%) dan kategori normal sebanyak 1 orang (33.3%). Kesimpulan : Dari 36 sampel pasien sectio caesarea dengan anestesi spinal didapatkan 3 pasien mengalami post dural puncture headache (8.3%).